Angiogenic properties of adipose tissue-derived multipotent mesenchymal stromal cells in patients with coronary heart disease - N. A. Dzhoyashvili; A. Yu. Efimenko; R. S. Akchurin; V. A. Tkachuk; E. V. Parfenova (Российский кардиологический журнал, 2013)
Aim. To compare angiogenic properties of adipose tissue (AT) derived multipotent mesenchymal stromal cells (MMSC) in patients with or without coronary heart disease (CHD) and to investigate potential effects of concomitant Type 2 diabetes mellitus (DM-2) on these properties. Material and methods. To extract AT MMSC, subcutaneous adipose tissue samples were obtained during a surgical intervention in 19 controls (individuals without cardiovascular disease or DM-2), 28 patients with CHD and DM-2, and 32 CHD patients without DM-2. Angiogenic properties of AT MMSC were assessed by the length of capillary-like structures formed by endotheliocytes on Matrigel in the presence of the conditioned AT MMSC medium. Growth factor gene expression was measured using the real-time polymerase chain reaction. Growth factor levels in the conditioned AT MMSC medium were measured using the enzyme-linked immunosorbent assay (ELISA). Results. In CHD patients, the total length of capillary-like structures, formed by endotheliocytes in the presence of the conditioned AT MMSC medium, was twice as low as in controls. However, there was no marked difference between CHD patients with or without DM-2. CHD patients did not demonstrate a reduction in the levels of main angiogenic factors, measured in the conditioned AT MMSC medium. On the contrary, the levels of some factors (VEGF, HGF, and PIGF) were elevated, as well as the levels of PAI-1. Conclusion. Angiogenic activity of secretion end-products of AT MMSC was reduced in CHD patients, compared to CHD-free individuals. The presence of concomitant DM-2 did not affect angiogenic properties of AT MMSC in CHD patients. Reduced angiogenic activity of AT MMSC could be due to increased PAI-1 production. PAI-1 suppresses the activity of plasminogen activators and, therefore, may have angiogenic effects. To confirm this hypothesis, further research is needed.